(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine Job Accomplishment and Job Satisfaction in the Work Performance of Non-Teaching Staff at Bestlink College of the Philippines. Job in Accomplishment had an average of 4.66, and the higher composite mean was 4.71. The composite mean for the workplace is lower, 4.62. While the respondents overwhelmingly supported the overall mean of 4.05 for Job Satisfaction safety, they received the highest composite mean of 4.16. The lowest composite mean for belongingness statements is 3.88. Out of fifty respondents at the time of the study, non-teaching staff at Bestlink College of the Philippines were selected as a sample. As a result, the institution has greatly benefited from the staff’s excellent work ethic, good communication, and regular attendance at work in terms of both job performance and high output. In order to encourage effective job performance, it is advised that universities and other post- secondary institutions should handle the issue of staff work attitude seriously.